THE FACT OF WOMANHOOD IN THE BOOK OF DEDE KORKUT IN THE CONTEXT OF GENDER ROLES (Third Sector Social Economic Review, 2020)
In this essay, it is dwelt on the fact of ‘womanhood’ as being a gender role in the Book of Dede Korkut which is one of the important literary works in Turkish literature. The question of how the identity of womanhood formed by biological and social role construction is situated in the Book of Dede Korkut epics is tried to get answered from the gender perspective. The relations of family-woman, woman-woman, woman-society, and woman-man in the Book formed the ‘acceptable womanhood’.  The research question is tried to get answered as making a discourse analysis in the epics of Dede Korkut, thus the phenomenon of womanhood and the acceptable womanhood of epics is depicted.
Keywords: The Book of Dede Korkut; culture; gender; womanhood; identity; epic literature